Selective area rare-earth doping of planar glass samples for monolithic integration of optically passive and active waveguides - Kow, S.T.; Yap, Y.; Pua, C.H.; Chong, W.Y.; Law, A.W.P.; Adikan, Faisal Rafiq Mahamd; Haseeb, A.S. Md. Abdul; Ahmad, Harith (Elsevier, 2010)
Successful demonstration of selective area doping of planar glass samples for monolithic integration of optically passive and active devices on a single chip is presented. Salt solution of erbium was delivered onto pre-sintered germano-silicate samples via a syringe. The samples were then consolidated to form dense glass layers containing regions doped with rare earth. Erbium tri-chloride solution, 0.1 M. was used during the solution doping phase, with the resulting erbium atomic percentage ranging from more than 0.1-0.4, increasing linearly with the number of drips applied. (C) 2008 Elsevier GmbH. All rights reserved.